2021
DOI: 10.3390/ijms22073532
|View full text |Cite
|
Sign up to set email alerts
|

Withholding of M-CSF Supplement Reprograms Macrophages to M2-Like via Endogenous CSF-1 Activation

Abstract: Macrophage colony-stimulating factor (M-CSF or CSF-1) is known to have a broad range of actions on myeloid cells maturation, including the regulation of macrophage differentiation, proliferation and survival. Macrophages generated by M-CSF stimulus have been proposed to be alternatively activated or M2 phenotype. M-CSF is commonly overexpressed by tumors and is also known to enhance tumor growth and aggressiveness via stimulating pro-tumor activities of tumor-associated macrophages (TAMs). Currently, inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Therefore, whether M2 macrophages modulate the expression of NOX2 in an indirect way needs further investigation. CSF1R is the receptor of CSF1 (also known as M-CSF) which performs as an essential regulator of macrophage activation, polarization and proliferation ( 59 ). Macrophages undergoing M-CSF stimulation are activated to a phenotype that could regulate angiogenesis and tissue remodeling ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether M2 macrophages modulate the expression of NOX2 in an indirect way needs further investigation. CSF1R is the receptor of CSF1 (also known as M-CSF) which performs as an essential regulator of macrophage activation, polarization and proliferation ( 59 ). Macrophages undergoing M-CSF stimulation are activated to a phenotype that could regulate angiogenesis and tissue remodeling ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…CSF-1R is thus a prime target for treating solid tumors such as prostate or breast cancer alone or in combination with chemotherapy [37] or radiation therapy [38]. Though targeting CSF-1R expression on TAM appears as a promising strategy [39], the beneficial effects still need to be further investigated [40][41][42]. Second, numerous studies have demonstrated that CSF-1R also drives tumor cell progression in several cancer types, including renal cell carcinoma [43], ovarian cancer [44], colorectal cancer [45], bladder cancer [46], mesothelioma [47], and melanoma [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the process of AS, due to sustaining inflammation response, macrophages are continuously recruited to lesion sites. Monocytes firstly differentiate to macrophages (M0) due to cytokines, such as M-CSF ( 17 ). Although the differentiation of monocytes to macrophages is unreversible, macrophages possess eminent plasticity, i.e., switching their phenotypes and functioning according to external signals ( 18 ).…”
Section: Different Phenotypes Different Outcomesmentioning
confidence: 99%